Pertumbuhan anak-anak usia 7-11 tahun di Surabaya: Ketidaksesuaian berat badan dengan referensi WHO - Sakina Sakina; Fundhy S I Prihatanto; Desy Purwidyastuti; Myrtati D Artaria (Masyarakat, Kebudayaan dan Politik, 2014)
Body size is strongly considered in making medical decisions, selecting medical instruments, drug dosing, and asessment of children’s growth. References of body size based on Caucasian population are widely used nowadays. Unfortunately, these references might have significant differences with others population. A specific study in Indonesian population is needed especially to make its own reference of growth. This research is aimed to get body weight (BW) data from children aged 7-11 years in Surabaya. This research was conducted to 656 children aged 7-11 years. Anthropometer was used to get BW data. Measurement was performed in the morning. All data were plotted to WHO growth chart. Based on the data percentils, we created BW growth chart for specific age and sex.We found an increasing trend with increasing age especially in girls. The increasing trend is better observed in girls. BW data which was plotted to WHO growth chart revealed that in many younger children had normal body weight and even overweight, unfortunately when entering pubertal age some of these children were underweight. Older children has lineary correlated with BW. Data plotting to WHO growth chart reveals that the younger children grew normally according to the reference, but then at later phase they did not follow the reference. This trend is similar to a previous studies, so that this strenghten our supposition that the difference between the WHO Growth Chart and the body growth of children in Indonesian area is not caused by lack of nutrition.